“Proyecto de Factibilidad para la Producción y Comercialización de Forros para asientos de vehículos livianos en la ciudad de Loja” - Vargas Guerrero, Jean Carlos (2025)
The present research, on the “Proyecto de Factibilidad para la producción y comercialización de forros para asientos de vehículos livianos en la ciudad de Loja” [Feasibility Project for the production and marketing of seat covers for light vehicles in the city of Loja], aims to determine the financial viability, such as the market, technical, financial study and financial evaluation at the time of offering a product that satisfies consumer tastes and preferences. In this project, the methodology used was descriptive with a mixed approach, the deductive and inductive method was applied; different techniques were used such as documentary review, a survey directed to owners of light vehicles, in addition, a sample of 379 surveys was calculated; then, an interview applied to direct competitors that exist in the market, and, finally, observation to analyze opportunities. In the market study, an unsatisfied demand of 9,780 sets of covers was identified in the first year; in the marketing plan, aspects related to the presentation of the product and how to introduce it to the market were specified. In the technical study, the production capacity was determined at 1,252 sets of covers per year, which will be valid for 5 years of the project's useful life. The company will be incorporated as a Limited Liability Company whose corporate name will be AliCar Premium Cía. Ltda.; The financial study details the investment amounting to $94,840.83; 85% of which is contributed by the partners and 15% financed by a bank; the sale price is $145.00 per set of covers, which is made up of 11 pieces, obtaining an income for the first year of $181,544.99. The values of the financial evaluation are: NPV of $140,340.36; the IRR with 55.32%; the RBC is $0.83 for each dollar invested; the PRC will be given in 3 years, 5 months and 8 days; In the sensitivity analysis, there is an increase in costs of 37.50% and a decrease in income of 21%, which means that these indicators represent that the project is feasible for its execution.